Compulsory treatment at home: an interview study exploring the experiences of an early group of patients, relatives and mental-health workers - D. A. de Waardt; I. C. de Jong; M. Lubben; I. Haakma; C. L. Mulder; G. A. M. Widdershoven (BMC Health Services Research)
Abstract Background When introduced in 2020, the Netherlands’ Compulsory Mental Healthcare Act included provisions for compulsory community treatment (CCT) and compulsory treatment in patients’ homes (CTH). Although CCT has been incorporated into mental health care in many countries, its effectiveness is debated. We know of no other countries in which CTH has been adopted. The aim of this study is to evaluate how an early group of participants experienced CTH. They were drawn from three stakeholder groups: patients, relatives and mental-health workers. Methods In total, 17 open interviews were conducted with six patients, five relatives and six mental-health workers. All had experience with CTH. Thematic analysis was used to analyze the interviews. Results Five themes were identified: 1). Reasons for applying for a court order with options for CTH. The reasons included preventing harm, avoiding hospitalization, and providing a safety net. 2.) Participants’ experiences with CTH in practice. The four most noteworthy experiences were related to the process of applying for a court order; compulsory home visits and the compulsory use of medication; the involvement of relatives during treatment; and the influence of CTH on the relationship between patients and relatives.  3.) The advantages and disadvantages of CTH. The most important advantages were avoiding hospitalization; improving medication adherence; facilitating easy access to care; early signaling of deterioration; early intervention; and regained autonomy. The most important disadvantages were restricted autonomy; fewer options for monitoring compared to hospitalization; and problems regarding control of patient behavior. 4.) Participants’ preferences. All preferred CTH to hospitalization. 5.) Participants’ suggestions for improving CTH. These included the need not only to provide patients with better information, but also to improve the involvement of relatives during treatment. Conclusion The interviewees found that CTH might help to avoid hospitalization by providing stakeholders with more options for arranging effective care at home. Although this suggests that initial experiences of CTH under the new Dutch mental health law were positive, it is still uncertain whether CTH as currently implemented really differs from CCT.